Expenditure efficiency of Local Government’s Basic Service Delivery in Nepal - Lamichhane, Hem Raj; Tamang, Govinda (International Journal of Operational Research/Nepal, 2019)
This study aims to compare the expenditure efficiencies of local government at the district level (DDCs). The study has used data regarding local governance and service delivery of 75 District Development Committees (DDCs) of Nepal from 2011/12 to 2015/16. Data Envelopment Analysis (DEA) has been used for measuring the expenditure efficiency of DDCs. Both input and output oriented models have been employed to measure the expenditure efficiencies. In both input and output oriented models, 29% DMUs are 100 per cent efficient under CRS approach and 25% DMUs are 100 per cent efficient under BCC approach. Moreover, Malmquist productivity index has been used to some selected DDCs in order to complement the findings regarding the expenditure efficiencies. The five years’ average Malmquist TFP index of Achham DDC has increased by 17% annually which was the highest performing DDCs. The five years’ average Malmquist TFP of 75 DDCs is calculated to be increased by 0.16% annually.